THE ROLE OF LANGUAGE IN SHAPING INTERGROUP RELATIONS: FOSTERING HARMONY IN MULTICULTURAL SOCIETIES - Yuliasari, Ulfa; Sari, Mella Mutika (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2022)
According to the literatures, language plays an important role in intercultural relationships in a multi-racial society. The research focuses on inclusive and respectful use of language as avenues to break down the civilizational gaps. The paper demonstrates that language is instrumental in enhancing mutual understanding, trust and social harmony. A literature review together with qualitative analysis is employed to show how effective and inclusive it is at bridging divisions between different people through which they collaborate. It also explores the barriers created by language differences that can carry on segregation among groups. This shows that for peaceful co-existence and multicultural societies, inclusive communication practices ought to be promoted.